THE NATURE OF PHONOLOGICAL AWARENESS DEFICITS OF LEARNERS IN CLASS SIX WITH READING DISABILITIES IN SELECTED SCHOOLS IN NAIROBI COUNTY-KENYA - O. STEPHEN, DR. ORAGO; EUNICE, DR. NYAMASYO; RUTH, DR. NDUNG’U (IJRDO - Journal of Social Science and Humanities Research, 2016)
This study set out to investigate the phonological awareness skills of learners with reading disability. These learners should be identified and be assisted so that they can proceed with their learning lives. A sample of pupils in class six from the selected schools in Nairobi County was used in the study. The Phonological Awareness Theory was used in this study. The data were obtained from tape - recorded texts from the respondents. Tape recorded data were transcribed, analysed and then discussed. Various deficits in phonological awareness were observed. These were categorized as mis-articulations of substitution, reading of the entire word instead of identifying the sounds; spelling the words and segmentation. The misarticulations were dominated by substitutions and atypical categories.